2020
DOI: 10.1007/978-3-030-49663-0_51
|View full text |Cite
|
Sign up to set email alerts
|

Learning Analytics Dashboard for Motivation and Performance

Abstract: Deploying Learning Analytics that significantly improve learning outcomes remains a challenge. Motivation has been found to be related to academic achievement and is argued to play an essential role in efficient learning. We developed a Learning Analytics dashboard and designed an intervention that relies on goal orientation and social comparison. Subjects can see a prediction of their final grade in a course as well as how they perform in comparison to classmates with similar goal grades. Those with access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
1
22
0
Order By: Relevance
“…Descriptive analytics content Conducted Aljohani et al, 2019;Baneres et al, 2019;Bodily et al, 2018;Chatti et al, 2020;Chen et al, 2019;Fleur et al, 2020;Gras et al, 2020;Han et al, 2021;He et al, 2019;Karaoglan Yilmaz & Yilmaz, 2020;Kia et al, 2020;Kokoç & Altun, 2021;Majumdar et al, 2019;Naranjo et al, 2019;Owatari et al, 2020;Ulfa et al, 2019;Valle et al, 2021 Predictive analytics content and reported accuracy Not conducted Aljohani et al, 2019;Bodily et al, 2018;Chatti et al, 2020;Chen et al, 2019;Gras et al, 2020;Han et al, 2021;He et al, 2019;Karaoglan Yilmaz & Yilmaz, 2020;Kia et al, 2020;Majumdar et al, 2019;Naranjo et al, 2019;Owatari et al, 2020;Ulfa et al, 2019Conducted Baneres et al, 2019Fleur et al, 2020;Kokoç & Altun, 2021;Valle et al, 2021 Accuracy not reported Fleur et al, 2020;Valle et al, 2021 80-89% accuracy achieved Kokoç & Altun, 2021 90-95% accuracy achieved Baneres et al, 2019 ...…”
Section: Analysis Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Descriptive analytics content Conducted Aljohani et al, 2019;Baneres et al, 2019;Bodily et al, 2018;Chatti et al, 2020;Chen et al, 2019;Fleur et al, 2020;Gras et al, 2020;Han et al, 2021;He et al, 2019;Karaoglan Yilmaz & Yilmaz, 2020;Kia et al, 2020;Kokoç & Altun, 2021;Majumdar et al, 2019;Naranjo et al, 2019;Owatari et al, 2020;Ulfa et al, 2019;Valle et al, 2021 Predictive analytics content and reported accuracy Not conducted Aljohani et al, 2019;Bodily et al, 2018;Chatti et al, 2020;Chen et al, 2019;Gras et al, 2020;Han et al, 2021;He et al, 2019;Karaoglan Yilmaz & Yilmaz, 2020;Kia et al, 2020;Majumdar et al, 2019;Naranjo et al, 2019;Owatari et al, 2020;Ulfa et al, 2019Conducted Baneres et al, 2019Fleur et al, 2020;Kokoç & Altun, 2021;Valle et al, 2021 Accuracy not reported Fleur et al, 2020;Valle et al, 2021 80-89% accuracy achieved Kokoç & Altun, 2021 90-95% accuracy achieved Baneres et al, 2019 ...…”
Section: Analysis Studiesmentioning
confidence: 99%
“…Conducted non-data driven Baneres et al, 2019;Bodily et al, 2018;Gras et al, 2020;Han et al, 2021;Karaoglan Yilmaz & Yilmaz, 2020;Majumdar et al, 2019 Not conducted Aljohani et al, 2019;Chatti et al, 2020;Chen et al, 2019;Fleur et al, 2020;He et al, 2019;Kia et al, 2020;Kokoç & Altun, 2021;Naranjo et al, 2019;Owatari et al, 2020;Ulfa et al, 2019;Valle et al, 2021 Model interpretability and explainablility…”
Section: Analysis Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-Regulated Learning (SRL) is the ability to plan, monitor, and actively control one's learning process (Zimmerman, 2002). According to SRL theory, motivation is critical to academic success (Fleur, Bos, and Bredeweg, 2020). LADs can motivate students and assist them in reflecting on their SRL process (Muldner et al, 2015).…”
Section: Self-regulated Learning and Lad Feedbackmentioning
confidence: 99%